FORMULATION AND EVALUATION OF AN ANTIMICROBIAL MUCOADHESIVE DENTAL GEL OF AZADIRACHTA INDICA AND GLYCYRRHIZA GLABRA - JAIN, HEMANT K.; SWAMI, PRERANA N.; GUJAR, K. N. (International Journal of Applied Pharmaceutics, 2019)
Objective: Objective of this study was to formulate and evaluate an antimicrobial mucoadhesive dental gel of herbal drugs for the prevention and treatment of dental plaque, dental caries, and periodontitis. Methods: Azadirachta indica leaves extract was prepared with ethanol: water (80:20 v/v) and Glycyrrhiza glabra roots extract was prepared with ethanol: water (30:70 v/v). Both the extracts were evaluated for organoleptic properties, pH, phytochemical screening and total phenolic content. Thin layer chromatography (TLC) and Reverse-phase high-performance liquid chromatography (RP-HPLC) studies were performed. Antibacterial activity of the extract was done on Mueller Hinton agar media against Streptococcus mutans using the disc diffusion method. A mucoadhesive gel was prepared using carbopol 934, polyethylene glycol (PEG) 400 as a bioadhesive polymer and penetration enhancer, respectively. Three gel formulations were prepared at various concentrations of carbopol 934. Dental gel formulations were evaluated for different parameters such as appearance, pH, viscosity, spreadabilty, syringeability. Optimised batch was used for further studies viz. stability study, drug content, diffusion study to determine percent cumulative release of drug from gel formulation and in vitro mucoadhesion study. Results: Rf value of nimbin and glycyrrhizin in TLC study, were found to be 0.08 and 0.56, respectively. RP-HPLC method was developed for estimation of active constituents present in both extracts using mobile phase acetonitrile: water [containing 0.1 % v/v glacial Acetic acid (GAA)]: methanol in the ratio of 30:60:10 at the flow rate of 0.8 ml/min. Rt of active constituents from both drug extracts was found to be 3.119 and 4.15 min, respectively. 2.5 % w/v of Azadirachta indica leaves extract showed a good zone of inhibition (10.66±0.577 mm) near to chlorhexidine (11.33±0.5773 mm). 1 % of Glycyrrhiza glabra roots extract exhibit antibacterial activity (9±1 mm) and masks the bitter taste of formulation. Batch (F2) was selected on the basis of viscosity, spreadabilty and syringeability. The optimised batch was found to be stable and has 83 % and 80.3 % of drug content. Percent cumulative releases of the drug from gel formulation during the diffusion study were found to be 87.52 % and 85.43 %. Adhesive force and adhesiveness were found to be 11.90 g and 0.92 millijoule, respectively during mucoadhesion study. Conclusion: The evaluation parameters of optimized batch indicate the prepared dental gel is mucoadhesive, stable, good delivery drug system containing antimicrobial agents for prevention of plaque formation, dental caries and periodontitis.